Phytochemistry Profile and Antioxidant Activity of Dumortiera hirsuta (Sw.) Nees from Gumitir, East Java - Farhan, Abdillah Maulana; Setyati, Dwi; Gilani, Noor Azizah; Su’udi, Mukhamad; Ulum, Fuad Bahrul (Bogor Agricultural University, Indonesia, 2025)
Dumortiera hirsuta, a thalloid liverwort, predominantly grows on the ground floor of coffee plantations in Gumitir, Jember District, East Java, and is known for its rich phytochemical content. This study aimed to comprehensively profile the volatile and non-volatile compounds present in the methanol extract of D. hirsuta and evaluate its antioxidant activity. The thallus was macerated using 96% methanol (1:10 ratio), followed by analysis using Gas Chromatography–Mass Spectrometry (GC–MS) and Liquid Chromatography–Mass Spectrometry Quadrupole Time-of-Flight (LC–MS QTOF). GC–MS identified 37 volatile compounds, with terpenes (29%), phenols (21%), and fatty acids (13%) as dominant classes. Several potent antioxidant sesquiterpenoids, including caryophyllene, guaiene, and aromadendrene derivatives, were notably abundant, along with unique compounds such as phytol, benzoic acid, pyrocatechol, and furanones. LC–MS analysis detected 15 non-volatile secondary metabolites, predominantly flavonoids (e.g., kaempferol-3-O-β-D-glucuronide, luteolin, leucocyanidin), phenolics (sesamol, euparin), and terpenoids (brefeldin A, E-p-coumaric acid), of which nine are well-documented for their antioxidant properties. These compounds were identified with high accuracy (mass error ±4 ppm) across positive and negative ion modes. Antioxidant potential was confirmed through the DPPH radical scavenging assay, which yielded a moderate IC₅₀ value of 101.13 ppm and a strong dose-response correlation (R² = 0.9526). The favourable microclimatic conditions of Mount Gumitir likely contributed to the phytochemical richness observed. Collectively, these findings highlight D. hirsuta as a chemically diverse bryophyte with promising antioxidant constituents, supporting its potential application in pharmacological development and natural antioxidant sourcing.